Effects of fixation on RNA integrity in a liquid-based cervical cytology setting. Issue 1 (27th April 2007) - Horvath, C; Boulet, G; Sahebali, S; Bogers, J; Depuydt, C; Vereecken, A; Vermeulen, T; Vanden Broeck, D
Abstract : Aims: Despite many improvements, cervical cancer screening is still subject to shortcomings. Diagnostic accuracy may improve by using molecular biological techniques, requiring RNA of superior quality. This study determined the effect of SurePath fixation on RNA integrity to assess the suitability of clinical samples collected in this medium for RNA-based molecular assays. Methods: RNA isolation was performed on fresh and fixed HeLa cells and exfoliated cervical cells fixed in SurePath. The RNA integrity was evaluated by analysis of ribosomal RNA as an indicator of quality. The effect of SurePath preservation on PCR amplification was evaluated by real-time reverse transcriptase (RT)-PCR. Results: In contrast to unfixed cells, SurePath-fixed cells yielded less and severely degraded RNA, as shown by the absence of ribosomal RNA bands. RNA derived from SurePath-fixed cells showed poor real-time RT-PCR amplification characteristics, as evidenced by the absent correlation between threshold values and log cDNA concentration. Conclusions: Implementation of molecular biology in a clinical context is on the rise and may alleviate shortcomings in current screening and diagnostics. This study shows that SurePath fixation gives rise to highly fragmented RNA with insufficient quality for further reliable analysis by standard real-time RT-PCR applications. The increasing prominence of molecular screening stresses the importance of this finding, which must be considered in relation to choice of an appropriate liquid-based cytology system.